2022
DOI: 10.3389/fphar.2021.781237
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling in Mice With CB1 receptor Deletion in Primary Sensory Neurons Suggests New Analgesic Targets for Neuropathic Pain

Abstract: Type 1 and type 2 cannabinoid receptors (CB1 and CB2, respectively) mediate cannabinoid-induced analgesia. Loss of endogenous CB1 is associated with hyperalgesia. However, the downstream targets affected by ablation of CB1 in primary sensory neurons remain unknown. In the present study, we hypothesized that conditional knockout of CB1 in primary sensory neurons (CB1cKO) alters downstream gene expression in the dorsal root ganglion (DRG) and that targeting these pathways alleviates neuropathic pain. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Cnr1 expression levels in DRG neurons are important for regulating pain hypersensitivity; Cnr1 cKO in DRG neurons causes pain hypersensitivity in mice (Liu et al 2021). Similarly, we observed that nerve injury diminishes Cnr1 expression in the DRG via G9a (Luo et al 2020), a cofactor of REST.…”
Section: Discussionmentioning
confidence: 99%
“…Cnr1 expression levels in DRG neurons are important for regulating pain hypersensitivity; Cnr1 cKO in DRG neurons causes pain hypersensitivity in mice (Liu et al 2021). Similarly, we observed that nerve injury diminishes Cnr1 expression in the DRG via G9a (Luo et al 2020), a cofactor of REST.…”
Section: Discussionmentioning
confidence: 99%
“…The CB2 receptor inhibitor AM630 (Sigma-Aldrich, St. Louis, United States) was dissolved in a vehicle consisting of 1:2:7 ratio of dimethylsulfoxide (DMSO), Tween 80 and normal saline as previously described (Liu et al, 2021). Mice were intraperitoneally administrated with 100 μl of AM630 at 5 mg/kg body weight (Lopes et al, 2020) or vehicle 30 min before EA treatment, every day for 7 days.…”
Section: Drug Administrationmentioning
confidence: 99%